Effect of the BH3 Mimetic Polyphenol (–)-Gossypol (AT-101) on the in vitro and in vivo Growth of Malignant Mesothelioma - Benvenuto, Monica; Mattera, Rosanna; Sticca, Joshua Ismaele; Rossi, Piero; Cipriani, Chiara; Giganti, Maria Gabriella; Volpi, Antonio; Modesti, Andrea; Masuelli, Laura; Bei, Roberto (Frontiers in Pharmacology, 2018)
Malignant mesothelioma (MM) is a primary tumor arising from mesothelial cells. The survival of MM patients following traditional chemotherapy is poor, thus innovative treatments for MM are needed. (‒)-gossypol (AT-101) is a BH3 mimetic compound which possesses anti-tumoral activity by targeting multiple signaling transduction pathways. Several clinical trials employing AT-101 have been performed and some of them are still ongoing. Accordingly, we investigated the in vitro effects of AT-101 on cell proliferation, cell cycle regulation, pro-survival signaling pathways, apoptosis and autophagy of human (MM-B1, H-Meso-1, MM-F1) and mouse (#40a) MM cell lines. In addition, we explored the in vivo anti-tumor activities of AT-101 in a mouse model, in which the transplantation of MM cells induces ascites in the peritoneal space. AT-101 inhibited in vitro MM cells survival in a dose- and time-dependent manner and triggered autophagy, but the process was then blocked and was coincident with apoptosis activation. To confirm the effect of AT-101 in inducing the apoptosis of MM cells, MM cells were simultaneously treated with AT-101 and with the caspase inhibitor, Z-VAD-FMK. Z-VAD-FMK was able to significantly reduce the number of cells in the subG1 phase compared to the treatment with AT-101 alone. This result corroborates the induction of cell death by apoptosis following treatment with AT-101. Indeed, Western blotting results showed that AT-101 increases Bax/Bcl-2 ratio, modulates p53 expression, activates caspase 9 and the cleavage of PARP-1. In addition, the treatment with AT-101 was able to: (a) decrease the ErbB2 protein expression; (b) increase the EGFR protein expression; (c) affect the phosphorylation of ERK1/2, p38 and AKT; (d) stimulate JNK1/2 and c-jun phosphorylation. Our in vivo results showed that the intraperitoneal administration of AT-101 increased the median survival of C57BL/6 mice intraperitoneally transplanted with #40a cells and reduced the risk of developing tumors. Our findings may have important implications for the design of MM therapies by employing AT-101 as an anticancer agent in combination with standard therapies.